Antecedents and consequences of teachers' goal profiles in Australia and Israel. (December 2021) - Watt, Helen M.G.; Butler, Ruth; Richardson, Paul W.
Abstract: Studies drawing on Butler's (2012) Goal Orientations for Teaching framework show mastery and relational goals are beneficial, ability-avoidance maladaptive and inconsistent effects for ability-approach. We adopt a person-centered approach to discern the extent to which teachers pursue different goal combinations. In two studies of mid-career primary and secondary teachers ( N s = 476 Australian, 507 Israeli) we assessed via self-report surveys: teachers' achievement goals, initial motivations to teach, school contexts, professional engagement and instructional practices. Latent profile analyses distinguished four goal combinations per sample. In both, mastery and relational goals covaried as 'task' goals. Profiles with stronger ability than task goals were maladaptive for teachers and teaching, and in the Australian sample linked with poor initial 'fallback' career motivation. Profiles with stronger task than ability goals were most adaptive, and linked to more positive school climate. Implications are outlined for theory and practice. Highlights: Teachers showed distinct goal profiles. Mastery and relational goals covaried as 'task goals' core to teachers' work. Profiles higher on task goals were adaptive for teachers and teaching. Profiles higher on ability goals were frequent and maladaptive. Maladaptive profiles linked to poorer perceived school climate and initial career motivation.